PENINGKATAN PEMAHAMAN HUKUM DAN KONSERVASI PENYU MELALUI PENDEKATAN EDUKASI DAN PARTISIPATIF DI DESA SIMATANG UTARA - Tiar Bustan; Nur Ikhsan; Firgiawan; Arina Silviana; Ika Wahyuni Putri (Makapande Mengabdi: Jurnal Ilmiah Pengabdian Kepada Masyarakat, 2025)
Turtles are ancient animals that play a vital role in maintaining the balance of marine ecosystems. However, their populations are increasingly threatened by the practice of egg harvesting and catching adult turtles in coastal areas, including North Simatang Village. This community service program aims to increase legal and ecological awareness among the community regarding the importance of turtle protection and to revitalize local wisdom values ​​in conservation. The methods used include field observation, legal outreach, ecological counseling, community-based conservation training, and the formation of Conservation Awareness Groups (KSK). The program was conducted over approximately two weeks, involving approximately 20 households and coastal community groups. The results of the community service program indicate an increase in legal and ecological understanding, a growing collective commitment to reducing turtle exploitation practices, and the emergence of sustainable conservation initiatives integrated into the Village Medium-Term Development Plan (RPJMDes). Thus, this program has proven effective in building collective awareness and strengthening the community's role in turtle conservation efforts at the local level.